Psychometric validation of the Dysmorphic Concern Questionnaire (DCQ) into Arabic - Feten Fekih-Romdhane; Rabih Hallit; Vanessa Azzi; Diana Malaeb; Fouad Sakr; Mariam Dabbous; Tabassum Rashid; Toni Sawma; Sahar Obeid; Souheil Hallit (Middle East Current Psychiatry, 2024)
Abstract Background Research on dysmorphic concerns (DC) in Arabic-speaking contexts is hampered by the lack of validated tools. Because DC are culturally dependent, psychometrically sound measures are needed at the national level to closely and accurately investigate the construct in specific societies and populations. The purpose of the current research was to investigate the psychometric properties of Dysmorphic Concern Questionnaire (DCQ) in its Arabic translation in Lebanese adults. Methods The study involved 515 participants (69.9% females, mean age of 27.55 ± 10.92 years) who completed a self-report, web-based questionnaire. Results Confirmatory factor analysis indicated excellent construct validity, as the one-factor structure of the Arabic DCQ fits well with the data. McDonald’s omega was 0.89 in our sample, evidencing an excellent level of internal consistency. Furthermore, the results from the multigroup analysis showed that the DCQ holds similar structural model between genders at the metric, configural, and scalar levels. Finally, DC levels correlated inversely with body appreciation and self-esteem and positively with disordered eating symptoms, thus supporting the concurrent and convergent validity of the Arabic DCQ. Conclusion The DCQ translated into Arabic appears to have a valid self-assessment measure to capture the presence of DC manifestations. It is anticipated that the Arabic DCQ will be advantageous for healthcare professionals and researchers working with Arabic-speaking people around the world.